Studi Komparasi Al-Qur’an dan Tripitaka: Landasan Moderasi Beragama untuk Kerukunan Masyarakat Indoneisa - Saputra, Eko; Noor, Muhammad Fauzi (Lembaga Yasin AlSys, 2024)
A number of surveys have shown a trend towards radicalism and intolerance, especially in relation to cases of harmony in social life between religious communities. This research aims to foster interfaith dialogue efforts by comparing the messages contained in the Holy Qur'an and Tripitaka as a basis for religious moderation. This research is a library research that uses a descriptive-comparative approach to observe the comparison of values and messages of religious moderation contained in the Qur'an and Tripitaka. The results show that in the implementation of the values in the Tripitaka, Buddhism emphasises the aspect of mysticism. In contrast, Islam in the Qur'an highlights the practical aspects that can be the foundation for living a just, harmonious and peaceful life.